Management of complications in penile prosthesis reimplantation: A case report - Camilla Capretti; Antonio Avolio; Alberto Florio; Silvia Giovannozzi; Domenico De Carolis (Archivio Italiano di Urologia e Andrologia, 2020)
A 74-years-old patient, without comorbidity, underwent malleable penile prosthesis (MPP) implantation in 2007. In 2015, after a perineal trauma, he experienced stress urinary incontinence, medial extrusion of the left prosthetic cylinder and an urethrocavernous fistula. The cylinder was removed and an artificial urinary sphincter (AUS) implanted, together with a three-component inflatable penile prosthesis (IPP). The left corpus cavernosum (CC) was significantly shorter than the right one due to fibrosis. After 8 months, partial lateral extrusion of the right prosthetic cylinder prompted a replacement with a shorter extensor. Six months after, a new diastasis of the ruptured area occurred due to a further CC shortening. The extensor was removed and the cylinder shortened, with a dermal graft applied to the area. Long-term patient satisfaction was high.